90 letnikov Časopisa za zgodovino in narodopisje - Stavbar, Vlasta (Časopis za zgodovino in narodopisje, 2020)
The treatise brings a short historical overview of the Časopis za zgodovino in narodopisje (The Review for History and Ethnography), which was published for the first time in 1904 as the gazette of the Historical Society for Lower Styria, and is still published today. It is issued by the Historical Society in Maribor and the University of Maribor Library. The article presents historical events, editors, editorial policy, contents, and the remarkable number of published articles. At its 115th anniversary, the published articles were collected in an extensive Bibliography of the Časopis za zgodovino in narodopisje for the period between 1904 and 2019.
Keywords: bibliografije; Časopis za zgodovino in narodopisje; zgodovina